Effectivity of probiotic, micromineral enriched yeast and their combination with Azadirachta indica leaves containing tannin on fermentability and digestibility of Pennisetum hybrid - Ahmad Sofyan; A. A. Sakti; M. F. Karimy; H. Julendra; L. Istiqomah; H. Herdian; E. Damayanti; A. E. Suryani (Indonesian Center for Animal Research and Development (ICARD), 2015)
Organic additive for animal had been explored to replace antibiotic growth promoter. Probiotic from lactic acid bacteria was widely used to support the microbial balances in digestive tract, while organic mineral was added into diets to improve bioavailability for preventing mineral deficiency disorders. This experiment was aimed to assess probiotic (Pediococcus acidilactici RS2) and micromineral enriched yeast (MEY) combined with tannin from neem (Azadirachta indica) leaves containing tannin on king grass (P. hybrid) fermentability using in vitro gas production technique. Treatments consisted of P0 (control/forage without additive), P1 (P0+MEY); P2 (P0+MEY+crude tannin); P3 (P0+Probiotic); P4 (P0+Probiotic+MEY), and P5 (P0+Probiotic+MEY+crude tannin). The study was arranged in a completely randomized design (CRD) with three replications in each treatment. Probiotic, MEY or tannin supplementation significantly increased (P<0.05) gas production without affecting volatile fatty acid, protozoa numbers, methane production and in vitro digestibility of forage. The highest cumulative gas production was found in forage treated by P4 followed by P5, P1, P5, P2, P3 and control. Kinetic of gas production was significantly affected by treatments after 8 h incubation. Although the treatments were only significantly affected gas production kinetic (b, c and total gas), the hierarchical cluster analysis indicated that some parameters consisted of acetate, propionate, in vitro digestibility, protozoa numbers, and methane production were closely correlated to the gas production kinetic parameters. It was concluded that either organic mineral supplementation or its combination with probiotic, and probiotic+tannin improved fermentabilty of forage without negative effect on in vitro digestibility.